Identify the susceptibility profile to measles in the general population: Serological survey of measles antibodies in Shaanxi province, China, in 2016. Issue 52 (19th December 2017) - Pei, Lin; Yang, Yuxuan; Zhao, Xiaodan; Zhang, Shaobai; Yuan, Lingyun; Liu, Yamei; Yu, Yan
Abstract: The reported coverage with two doses of the measles vaccine (MCV) in Shaanxi Province, China, is greater than 95%, but the measles incidence over the whole province remains high. Cross-sectional serological surveys of measles antibodies in Shaanxi Province were conducted in 2016 to assess the population's immunity. The measles IgG levels were measured in serum samples using ELISA. The geometric means concentration (GMC) levels and seroprevalence rates with 95% CIs were calculated by region, gender, and age. A total of 3574 serum samples were collected from participants aged from 2 months to 49 years. The GMC of measles antibodies was 471.3 mIU/ml (95% CI: 445.9–498.2 mIU/ml), and the seroprevalence was only 85.9% (95% CI: 84.8–87.1%). A significant difference in the GMC (P < .05) but not the seroprevalence (P > .05) was observed among the 3 regions. The report measles incidences were high in individuals aged 0–7 months (33.2/100 000) and 8–17 months (26.8/100 000). Although both measles immunity (90.7%) and MCV coverage (89.7%) were low in children aged 8–17 months, the measles seroprevalence in adults was high at greater than 90%. These results revealed that further actions may be taken to increase vaccination coverage in children aged 8 months to 5 years over the whole province and teenagers in the south region. In particular, timely administration of the first MCV dose should be emphasized to prevent measles epidemics in children aged 8–17 months. Vaccination strategies may be varied by age and region.